Describing biomarkers for Alzheimer's disease: Localization of amyloid‐β in the retina. (20th December 2022) - Lee, Sieun; Xu, Qinyuan (Alis); Boerkoel, Pierre; Hirsch‐Reinshagen, Veronica; Mackenzie, Ian R; Hsiung, Ging‐Yuek Robin; Charm, Geoffrey; To, Elliot; Liu, Alice; Schwab, Katerina; Jiang, Kailun; Sarunic, Marinko; et al.
Abstract: Background: Retinal glial cells, Aβ deposition and their colocalization were examined in post‐mortem retinal cross‐sections of Alzheimer's disease (AD) donors and age‐matched controls. Method: Immunohistochemistry was performed on paraffin‐embedded cross‐sections of central and mid‐peripheral retinal tissues of AD donors (n = 9) and age‐matched controls (n = 12) to detect Aβ (6F/3D, 12F4, and 6E10) with neuronal profile (TUBB), astrocytes and Muller cells (GFAP), and microglia (IBA‐1). Astrocytes and Muller cells were further distinguished by double‐labelling of GFAP and glutamine synthetase (GS) antibody. The tissues were imaged with a confocal microscope and the degree of immunoreactivity and colocalization were measured layer‐wise and compared (α=.05) between the AD and control groups. Result: The AD group showed more Aβ load in the mid‐peripheral retina but not central retina. For glial cells, less GFAP immunoreactivity in the central and mid‐peripheral retina and more microglia immunoreactivity in the mid‐peripheral retina were observed in the AD group. In the double‐labelling of GFAP and GS, activated Muller cells (labelled by GFAP and GS) were reduced in the AD group but not astrocytes (labelled only by GFAP). The AD group also showed greater co‐localization of Aβ with neuronal profile but less with microglia. Conclusion: The reduced Muller cell metabolism and increase amount of microglia but with reduced colocalization with Aβ indicate complex glial dysfunction in the AD retina.